Barthes, a philosophical work - García Soto, Luis (Escritura e Imagen, 2021)
In this article, I present and develop a reading and interpretation hypothesis, in a philosophical way, of Roland Barthes’s work. My starting point is to examine the sign, in its different manifestations (specifically, words and images and their combinations) and dimensions (sign, signifier, signified, referent), in its relationships with the real, i.e., as appearance and / or appearance of the real, as it appears in Barthes’ texts. In my opinion, in his writings, it is possible to point out four lines of work (criticism, science, aesthetics, ethics), linked by a common denominator of philosophy. In sum, without excluding other interpretations, I try to defend the plausibility of seeing Barthes as a philosopher and reading his work as a philosophy.
Keywords: Barthes; philosophy; criticism; science; aesthetics; ethics